Peningkatan Kompetensi Dasar Akuntansi Kelompok UMKM (Kompeten) di Bekasi - Vinola Herawaty; Prima D. Andrian; Ayu Aulia Oktaviani (Penerbit Goodwood, 2021)
The purpose: The purpose of this community service (PKM) is to improve understanding and ability of the Basic Accounting Competencies starting from the accounting cycle to financial reporting for MSME. Method: This PKM activity is carried out using the tutorial method and discussion on the concept of Basic Accounting covering the accounting cycle to financial statements. The target of these trainees is Komunitas Perempuan Tangguh Nasional (KOMPETeN), which is a community forum for housewives who have entrepreneurs, with the aim of helping to develop an entrepreneurial spirit, strengthening the role of women in MSMEs, opening access to permits and training to develop MSMEs, open access to global marketing, and create synergies among fellow members and members with other parties.. The implementation of this training activity is intended to increase the participation of the Program Pendidikan Profesi Akuntan FEB Usakti in helping to improve human resource competence, especially for Komunitas Perempuan Tangguh Nasional (KOMPETeN) in Indonesia. This activity was carried out on March 16, 2021 online through Zoom Meeting. Results: Based on the evaluation, after following this PKM (1) The participants understand the basic accounting and basic transactions for MSMEs; (2) Participants can understand the financial statement especially income statement for MSMEs; and (3) The participants can prepare the income statement for MSMEs. Conclusions: There are improvements of MSME entrepreneurs’ competence in terms of the Basic Accounting for Komunitas Perempuan Tangguh Nasional (KOMPETeN).